Trap Designs, Colors, and Lures for Emerald Ash Borer Detection - Poland, Therese M.; Petrice, Toby R.; Ciaramitaro, Tina M. (Frontiers in Forests and Global Change, 2019)
The emerald ash borer, Agrilus planipennis, is the most damaging invasive forest insect pest ever to have invaded North America. It is native to Asia and is established in the United States, Canada, European Russia and Ukraine where it threatens native ash across North America and Europe. We evaluated trap designs, colors, and lures for A. planipennis detection at sites with varying infestation levels. Sticky prism traps and multiple funnel traps (purple and green) hung in the canopy of ash trees and double-decker traps had high capture rates even at sites with very low infestation levels. At a low infestation site, females were more attracted to dark purple sticky prism traps hung in the canopy and to Manuka oil and Phoebe oil lures than to light green sticky prism traps or cis-3-hexenol lures; whereas, males were more attracted to light green sticky prism traps in the canopy and cis-3-hexenol lures than to dark purple sticky prism traps or Manuka and Phoebe oil lures. More males and females were captured in double-decker traps with dark green upper prisms and light purple lower prisms, baited with cis-3-hexenol, than in double-decker traps with dark purple upper and lower prisms. Dark green funnel traps and double-decker traps with dark green upper and light purple lower prisms baited with cis-3-hexenol lures captured more females than dark green sticky prism traps hung in the canopy at sites with very low infestation levels. Detection rates were similar among trap types and ranged from 75-80% for dark green sticky prism traps, 82.5-100% for dark green funnel traps, and 100% for double-decker traps with dark green upper and light purple lower prisms at sites with very low population densities. Each trap type has different advantages and disadvantages in terms of costs, ability to reuse the traps, and ease of deployment. These and other factors including trap placement, host density and condition should be considered in selecting traps for operational surveys. Future research is needed to determine effective trapping radius, relationship of trap catches to population density, cost benefit of different trap types, and optimal deployment strategy.